Training recommendations to improve repeated-sprint ability in Australian Football athletes - Brown, P. J. (Journal of Australian Strength and Conditioning, 2017)
This study reviewed the literature discussing repeated sprint ability (RSA) in Australian Football (AF) in order to create recommendations that coaches can apply in the field. The review was conducted at the University of Canberra Library using books, journals and online journals. Movement demands of AF were examined with results showing that the current RSA testing practice of 6x30m is not sport specific. A revised test of 10x20m is proposed, as this more accurately represents the movement demands of AF. Understanding the fatigue mechanisms that underpin RSA, and how best to train them is vital. Training should incorporate a wide variety of interval running, with work to rest ratio`s varying from 1:10 with 30 seconds work, to 2:1 with 120 seconds work. Specific RSA drills such as 3 x ([2 x 10, 15, 20m sprint: 15 sec rest]: 4.5 min rest) should be included. Undulating resistance training programs should be implemented to improve strength, power and muscle endurance. The repetition range will vary depending on specific athlete`s needs and training history. Plyometric training, including weighted sled sprints, are essential to improve the stretch shortening cycle and increase acceleration. A maximum of 140 landings per session during pre-season and a maximum of 100 landings in season are advised. Incorporating small sided games (SSG) into training sessions can improve RSA whilst concurrently training match awareness and skills. One proposed SSG session is a 4 vs. 4 game, duration 6 x 4 minutes performed at >90% maximum heart rate with 3 minutes active recovery at <60% maximum heart rate. Specific details are provided for each of these training modes and where possible have been adapted specifically for AF.